1976
DOI: 10.1002/jsfa.2740270709
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid digestibility studies of autoclaved rapeseed meals using an in vitro enzymatic procedure

Abstract: An investigation of in vitro enzymatic amino acid digestibility of autoclaved rapeseed meals using the enzyme pronase is presented. A correlation coefficient of 0.991 was obtained when comparing in vitro "available" lysine with "Silcock available" lysine. Autoclaving of rapeseed meal for periods of 15, 30, 60, 120 and 180 min at 103 kPa and 120°C caused the following chemical changes. Lysine, methionine and cysteine in vitro digestibilities were markedly decreased as to a lesser extent were the other amino aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0
1

Year Published

1979
1979
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 19 publications
1
7
0
1
Order By: Relevance
“…Thus, increasing toasting temperature from 90 to 100°C, after high moisture conditioning of the seeds, induced much more damage to total and available lysine than toasting at 120°C with lower moisture of seeds. This is in agreement with the earlier observations in which the moisture and height of temperature were found to play essential role in decreasing lysine concentration and availability in RSM (Josefsson, 1975;Rayner and Fox, 1976;Craig and Broderick, 1981;Pickard et al, 1986;Katzer and Minkowski, 1989). \ Laboratory studies (Raczyhski and Buraczewski, 1973;Hurrell and Carpenter, 1977) also clearly showed that decrease of lysine availability in heated protein is associated with an increase of moisture, in particular in the presence of reducing sugars.…”
Section: Discussionsupporting
confidence: 93%
“…Thus, increasing toasting temperature from 90 to 100°C, after high moisture conditioning of the seeds, induced much more damage to total and available lysine than toasting at 120°C with lower moisture of seeds. This is in agreement with the earlier observations in which the moisture and height of temperature were found to play essential role in decreasing lysine concentration and availability in RSM (Josefsson, 1975;Rayner and Fox, 1976;Craig and Broderick, 1981;Pickard et al, 1986;Katzer and Minkowski, 1989). \ Laboratory studies (Raczyhski and Buraczewski, 1973;Hurrell and Carpenter, 1977) also clearly showed that decrease of lysine availability in heated protein is associated with an increase of moisture, in particular in the presence of reducing sugars.…”
Section: Discussionsupporting
confidence: 93%
“…As in the present experiment, they found that in vitro digestibility values of protein were closely related to in vivo values. Rayner & Fox (1976 found that pronase was also effective in releasing amino acids from rapeseed meal and beef muscle, and that the amount of lysine released was related to the amount of chemically reactive lysine. In the present study, grains of known true ileal digestibility of N and availability of amino acids were used as reference standards.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the in vitro values were of little meaning by themselves as relative indices of digestibility and rely on calibration using standard relationships with values that are biologically meaningful. For example, there would be little value in using chemically reactive lysine values to calibrate in vitro digestibility values for grains, as Rayner & Fox (1976 have done for rapeseed meal and meat, since reactive-lysine content is not necessarily related to available lysine content of cereals . Saunders &Kohler (1972) related in vitro N digestibility andfaecal N digestibility.…”
Section: Discussionmentioning
confidence: 99%
“…Технічним способом теж вдається значно покращити якість ріпакового шроту (тостурування, екструзія, мікронізація і ін.). Однак недоліком останнього є необхідність дії високих температур, які призводять до зниження розчинності протеїну та доступності амінокислот [9].…”
Section: літературний оглядunclassified